A survey on the students exam anxiety in the Fatemeh (PBUH) College of Nursing and Midwifery Spring 2004 - Zahra Moaddeli; Mahrokh Ghazanfari Hesamabadi (Kerman University of Medical Sciences, 2005)
Background: Nowadays since a hard educational competition can be seen among students exam anxiety is increasing Anxiety causes concentration deviation so that data processing will decrease Also previous studies have shown pessimistic thoughts make the students to expect failure so that the student can not concentrate on the exam and as a result he will not get a positive result Objective: To determine the level of students exam anxiety in Fatemeh (PBUH) College of Nursing and Midwifery Methods: This analytic descriptive study was done on 317 students educating in Fatemeh College of Nursing and Midwifery A questionnaire consisting of 24 background questions and Spilbergers anxiety test with 32 questions were used to gather the data These questionnaires were given to the students in the exam salon before the final exam Measures of central tendency dispersion index ttest and one way ANOVA were used to analyze the data Results: The findings showed that 909% of the students had anxiety in low level 64% had in medium level and 17% had a high level anxiety The mean ( ± standard deviation) of exam anxiety of the students was 2576% (±1659) The mean (±standard deviation) of exam anxiety among the nursing students was 252 (±1645) and among the midwifery students it was 2678 (±169) but no significant difference was found between exam anxiety in terms of major (P>005) A significant difference was observed in anxiety level in terms of sex marital status parents education and the number of siblings Conclusion: Using consultation strategies and making a friendly intervention between students and teachers is recommended for the students with high level of test anxiety to identify the problems and try to solve them To relieve anxiety consultation interventions by specialists relaxation using comics and jokes in exams will be helpful